2020
DOI: 10.21608/aasj.2020.43599.1038
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability and genetic parameters of some white maize (Zea mays L.) inbred lines using diallel analysis

Abstract: Nine inbred lines (S 5) of white maize derived from Giza-2 and IW-469 were crossed using of half diallel cross mating design, during spring season of 2019 at the Farm of Faculty of Agriculture, Al-Azhar University at Assiut Branch, to produce thirty six F 1 crosses. The parents, crosses and tow checks i.e. SC-163 and SC-10 were evaluated during spring season of 2020 in R.C.B.D with three replications to determine combining ability, heterotic and gene action effects. Significant differences were found among par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
5
1
0
Order By: Relevance
“…The ratio of σ 2 GCA/σ 2 SCA after subtraction the environmental effect of both GCA and SCA variances as estimated according to Singh and Chaudhary (1979) was less than one for all the studied traits, indicating the non-additive gene action played the major role in the inheritance of all the studied traits, therefore selection procedure in the late or advanced generations will be very important to improve these traits. These obtained results are in the same line with those obtained by Haddadi et al (2012), Amin et al (2014), Azad et al (2015), Hassan et al (2019), El Hosary (2020), Hemada et al (2020) and El-Shahed et al (2021).…”
Section: Analysis Of Variancesupporting
confidence: 92%
See 2 more Smart Citations
“…The ratio of σ 2 GCA/σ 2 SCA after subtraction the environmental effect of both GCA and SCA variances as estimated according to Singh and Chaudhary (1979) was less than one for all the studied traits, indicating the non-additive gene action played the major role in the inheritance of all the studied traits, therefore selection procedure in the late or advanced generations will be very important to improve these traits. These obtained results are in the same line with those obtained by Haddadi et al (2012), Amin et al (2014), Azad et al (2015), Hassan et al (2019), El Hosary (2020), Hemada et al (2020) and El-Shahed et al (2021).…”
Section: Analysis Of Variancesupporting
confidence: 92%
“…These results agreed with the findings of Mohamad et al (2007), Dawod et al (2012), Wannows et al (2012), Dar et al (2017), Al-Rawi et al (2018, Ali (2020) and Hemada et al (2020).…”
Section: Genetic Variance Componentssupporting
confidence: 90%
See 1 more Smart Citation
“…The ratio of σ 2 GCA/σ 2 SCA after subtraction the environmental effect of both GCA and SCA variances as estimated according to Singh and Chaudhary (1979) was less than one for all the studied traits, indicating the non-additive gene action played the major role in the inheritance of all the studied traits, therefore selection procedure in the late or advanced generations will be very important to improve these traits. These obtained results are in the same line with those obtained by Abdel-Moneam et al (2009), Attia et al (2013), Ali (2016), Azad et al (2015), Hassan et al (2019), El Hosary (2020), Hemada et al (2020) and El-Shahed et al (2021).…”
Section: Analysis Of Variancesupporting
confidence: 91%
“…Partition sum of squares due to crosses into its components showed that mean squares due to GCA and SCA was highly significant for all the studied traits, indicating the importance of both additive and non-additive gene actions in the inheritance of all the studied traits. These obtained results could be supported with the findings by Aly and Mousa (2011), Attia et al (2013), Singh et al (2014), Sultan et al (2016), Gamea et al (2018), Anees et al (2019), Hussain et al (2019), Ali (2020), Hemada et al (2020) and El-Shahed et al (2021).…”
Section: Analysis Of Variancesupporting
confidence: 86%